Interest Rate and Loan Portfolio Performance of Commercial Banks in Uganda: Case of Stanbic Bank. - Mwebesa, Samson (Kabale University, 2023)
The study was about interest rate and loan portfolio performance of commercial banks in Uganda with a reference to Stanbic Bank, Kampala. The major objective of the study was to establish the relationship between interest rates and loan performance in commercial banks in Uganda. The specific objectives were to establish the effect of central bank rate on loan performance in Stanbic Bank, Kampala head office; to investigate the effect of prime lending rate on loan performance of commercial banks in Uganda; and, to establish how collateral affect portfolio performance in commercial banks. The study adopted a cross-sectional design. The study population included Credit Officers, Client Relationship Managers, Credit Evaluation Managers, and Branch managers. A sample of 108 units was selected from 150 units using both simple random and purposive sampling techniques. Data were collected using self-administered questionnaires, and personal interviews. Data were analysed using multiple regression, aided by SPSS version 23. The findings show that the effect of prime lending on loan portfolio performance is that Central bank rate and collateral security have non-significant effects on loan portfolio performance. The study concludes that commercial banks in Uganda that vary their interest rates show superior loan portfolio performance.Byimplication, interest rates remain a key driver of portfolio performance. From a policy perspective, commercial banks should empower their credit officers with knowledge of the portfolio’s composition and its inherent risks. This can guide customers on the time of loan application as well as during the time of loan portfolio monitoring.